2015
DOI: 10.1038/nature14186
|View full text |Cite
|
Sign up to set email alerts
|

Loss of δ-catenin function in severe autism

Abstract: SUMMARYAutism is a multifactorial neurodevelopmental disorder affecting more males than females; consequently, under a multifactorial genetic hypothesis, females are affected only when they cross a higher biological threshold. We hypothesize that deleterious variants at conserved residues are enriched in severely affected patients arising from FEMFs (female-enriched multiplex families) with severe disease, enhancing the detection of key autism genes in modest numbers of cases. We show the utility of this strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
170
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 148 publications
(179 citation statements)
references
References 55 publications
8
170
0
1
Order By: Relevance
“…This methodology may even be applied to genes that have not been previously implicated in ASD. For example, CTNND2 was recently implicated as a critical gene in autism based on studies of female-enriched multiplex families (Turner et al 2015) but was not found in any of the gene lists used for the current study. Its mouse ortholog has seven adjacent TBR1-bound regions and a low LoF burden.…”
Section: Tbr1 Regulates Autism Risk Genesmentioning
confidence: 80%
“…This methodology may even be applied to genes that have not been previously implicated in ASD. For example, CTNND2 was recently implicated as a critical gene in autism based on studies of female-enriched multiplex families (Turner et al 2015) but was not found in any of the gene lists used for the current study. Its mouse ortholog has seven adjacent TBR1-bound regions and a low LoF burden.…”
Section: Tbr1 Regulates Autism Risk Genesmentioning
confidence: 80%
“…25 Wnt signaling is a critical developmental pathway; the zebrafish is a tractable model in which to study Wnt output [26][27][28][29][30][31] and to interrogate alleles relevant to neurocognitive traits. 32 We tested several representative missense variants, including the female-specific de novo vari- was chosen as a negative control (rs375996245; MAF < 0.002).…”
mentioning
confidence: 99%
“…Our data also suggest that the genetic architecture of DDX3X-mediated pathology in males is different. All 7,9,23,24,26), a wide nasal bridge and/or bulbous nasal tip (e.g., individuals 11,13,15,16), narrow alae nasi and/or anteverted nostrils (e.g., individuals 2, 8,9,12,14,18,24,27,32,35), and hypertelorism (e.g., individuals 5,7,8,20,27). Informed consent was obtained for all 30 individuals shown.…”
mentioning
confidence: 99%
“…Small exonic deletions of CTNND2 have also been reported in individuals with low normal IQ and learning problems with or without autistic features or developmental delay [Asadollahi et al, 2014]. In addition, a recent study identified that deleterious variants in the CYFIP1, DLG1, PLXNA3, and CTNND2 genes are enriched in severely affected patients in female-enriched multiplex families (FEMFs) with severe autism and demonstrated the loss-of-function effect of CTNND2 in autism and neurodevelopment by in vivo and in vitro functional analyses [Turner et al, 2015].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, PLXNA3, with enriched variants in FEMFs, encodes a receptor for SEMA5A [Turner et al, 2015], which is located distal to CTNND2 (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%